Gender-based media platform adjustment and achievement of students in senior secondary school mathematics in Rivers West Senatorial District - Frank, Akeodi; Ndimele, Stanley Chimezie; Obushi, Lilian (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study investigated gender-based media platform adjustment and achievement of students in senior secondary school mathematics in Rivers West Senatorial District. A descriptive survey research design was adopted. Two null hypotheses guided the study. The population of the study was all the senior secondary school two students in Rivers West Senatorial District. The sample of the study was 400 students (200 males and 200 females) selected from 8 schools through the simple random sampling technique. The Media Platform Learning Adjustment Scale and Mathematics Achievement Test were developed by the researchers for data collection. While the Mathematics Achievement Test was given to an expert in Mathematics Education, the Media Platform Learning Adjustment Scale was given to two experts in Measurement and Evaluation and Technology Education at Ignatius Ajuru University of Education, Port Harcourt for face and content validations. The alpha coefficient index for the Media Platform Learning Adjustment Scale was 0.74 using R-studio, while the Mathematics Achievement Test yielded a reliability coefficient of 0.76 by the test-retest method. An Independent sample t-test was used to test the null hypotheses at a 0.05 level of significance. Results showed that: Male and female students do not significantly differ in their adjustment to media platform instruction. It was also found that both male and female students do not significantly differ in their mathematics achievement due to their adjustment to media platform instruction. It was recommended that schools should incorporate media platform instruction in their academic calendar for continuous learning and improvement in mathematics achievement among students.